Implementation of Inclusive Closed Loop in Improving Production Efficiency and Sustainability - Endarwan, Hendy; Rasyid, Aliy; Etwanto, Gary Putra (Indonesian Operations Research Association (IORA), 2025)
Amidst increasing external pressures related to sustainability, such as international regulations, stakeholder expectations, and global consumer demands, the rubber industry is required to develop internal strategies that are not only operationally efficient but also adaptive to the transformation towards environmentally friendly production and supply chain practices. This study aims to analyze the implementation of an inclusive closed-loop supply chain as a strategic approach for companies to integrate production efficiency, waste reduction, and respond to institutional pressures for sustainability. The novelty of this study lies in the integration of an inclusive closed-loop approach that goes beyond the traditional concept of recycling, prioritizing the active participation of all internal actors (production, procurement, sustainability) and strengthening cross-functional relationships within the organization as the basis for the transition to a green supply chain. This research is built on a combined theoretical framework: the Natural Resource-Based View (NRBV) to explain internal capabilities in creating a competitive advantage based on sustainable resources; Institutional Theory to identify the influence of external pressures on organizational behavior; and Stakeholder Theory to explore the dynamics of expectations and the involvement of key actors in the value chain. The method used is a quantitative explanatory approach, with data collection through a survey of managers at rubber processing companies in Indonesia. Data were analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS) to examine the relationships between inclusive closed-loop dimensions, operational efficiency, green supply chains, and companies' strategic adaptation to sustainability pressures. The expected results indicate that inclusive closed-loop supply chains contribute significantly to achieving operational efficiency and waste reduction, while strengthening companies' capabilities in building environmentally friendly supply chains and production processes. These findings are expected to provide theoretical contributions to the development of resource- and institutional-based sustainability strategies, as well as practical implications for companies responding to global challenges through inclusive and sustainable business model transformations.